Therapeutic potential of Gac fruit aril carotenoid extracts against diet induced obesity and audiogenic gene expression in rat - Mohd Nazri Abdul Rahman; Amin Ismail; Azrina Azlan; Ahmad Fazli Abdul Aziz; Mohd. Hafidz Mohd. Izhar; Nor Hayati Muhammad; Yoshito Ando (Penerbit Akademia Baru, 2025)
Momordica coincidences L. Spreng (Gac) is rich in carotenoids, yet its potential anti-obesity effects remain underexplored. This study aimed to evaluate the effects of Gac aril carotenoid-rich extract (GACRE) on biochemical markers, adipose tissue characteristics organ histology and the expression of obesity-related genes (PPARγ, C/EBP and UCP1) in high-fat diet (HFD)-induced obese Sprague Dawley rats. Thirty-two male rats were randomly assigned into four groups: G1 (normal diet, ND), G2 (HFD), G3 (HFD + GACRE 50 mg/kg) and G4 (HFD + GACRE 200 mg/kg) for eight weeks via oral gavage. Although GACRE supplementation did not significantly reduce body weight or adipose tissue mass, rats in the GACRE-200 group exhibited significantly lower levels of aspartate transaminase (AST), triglycerides, creatine kinase and fasting blood glucose (reductions of 32.17%, 22.16% and 31.30%, respectively). Both GACRE-treated groups showed a ~50% reduction in creatinine levels, with no notable changes in amylase, lipase, alanine transaminase (ALT) or bilirubin levels. Histological examination of liver tissues revealed micro-vesicular steatosis and sinusoidal changes in the GACRE-200 group. Gene expression analysis showed elevated PPARγ and UCP1 levels in brown adipose tissue (BAT) compared to white adipose tissue (WAT), correlating with a higher BAT mass and enhanced thermogenic potential. These findings suggest that GACRE at 200 mg/kg exerts modest therapeutic effects against obesity-related metabolic disturbances, primarily mediated through BAT activation and adaptogenic gene modulation.